Vulture roosting attendance in the southeastern United States - Partridge, Hannah C; Gagné, Sara A (PANGAEA, 2023)
Changes in landcover and habitat, especially related to urbanization, can impact species in various ways. Cathartid vultures, including the black vulture (Coragyps atratus) and the turkey vulture (Cathartes aura), have adapted to living in urban areas and are likely exposed to higher levels of urbanization and more frequent changes in habitat and landscape features. We examined how local and landscape features affect the roosting attendance of black vultures and turkey vultures to understand what factors impact vulture site selection and landscape use. We surveyed a total of twenty-nine overnight vulture roosts across the Charlotte Metropolitan Area, USA once a month between November and March from 2019-2021. During each survey, we counted the number of black vultures and turkey vultures roosting at the site. At each roosting site, we measured the temperature, wind speed, cloud cover, roost height, open space, and distance to water. In ten landscapes ranging from 0.4 km to 20 km radii surrounding the roost, we also measured developed landcover, developed-forest edge density, and landfill density. Analyses suggest that black vultures and turkey vultures are roosting in larger numbers in areas with less open space, near water, and in landscapes with more continuous forest landcover. As food availability is likely a major determinant of vulture presence, future research should investigate the food source most commonly used by vultures across urban and rural landscapes and the roosting site selection as it relates to food availability.
Keywords: black vulture; roost; turkey vulture; urbanization